PENGARUH PENDEKATAN TAKTIS TERHADAP KETERAMPILAN SHOOTING PADA TIM SEPAK BOLA SMA NEGERI 3 PEKANBARU - Erik Kurniawan; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to investigate the effect of session 10: model photo training exercises on a Tactical Approach to shooting skills in the Pekanbaru 3 High School Football Team. This research was conducted in the Da'wah field, Jalan Paus (Da'wah mosque complex) Rumbai, Pekanbaru. When the study was conducted July 13 2019 to August 21 2019. The population in this study was the Soccer Team of SMA Negeri 3 Pekanbaru, with a total of 16 students. The entire population was taken as a sample, so the number of samples was 16 people. The data collection technique in this study is the initial test which is a reference for conducting research. Then the final test was carried out after 16 treatments were carried out. After 16 meetings, the researcher will conduct a final test similar to the initial test, the ball shooting test. From the results Before the analysis was carried out, the pree test was carried out with an average yield of 51.65, then the Tactical Approach training model was conducted during 16 meetings in Soccer SMA Negeri 3 Pekanbaru totaling 16 people. Obtained average post-test results 54.25. Based on the statistical analysis of the t test, a difference value of 2.6 was obtained and resulted in a tcount of 5.51 and 1.753 table. Means tcount> ttable. It can be concluded that the Tactical Approach carried out for 16 times has an Influence on the Boot Skills of 3 Soccer Players in SMA Negeri Pekanbaru. Key Words: Tactical Approach, Shooting Skills